2014
DOI: 10.1158/1940-6207.capr-13-0318
|View full text |Cite
|
Sign up to set email alerts
|

Low Integrated DNA Repair Score and Lung Cancer Risk

Abstract: DNA repair is a prime mechanism for preventing DNA damage, mutation, and cancers. Adopting a functional approach, we examined the association with lung cancer risk of an integrated DNA repair score, measured by a panel of three enzymatic DNA repair activities in peripheral blood mononuclear cells. The panel included assays for AP endonuclease 1 (APE1), 8-oxoguanine DNA glycosylase (OGG1), and methylpurine DNA glycosylase (MPG), all of which repair oxidative DNA damage as part of the base excision repair pathwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…So far a lack of standardization and clinical validation, together with the relatively low throughput and labor-intensive nature of most methods of measuring DRC have precluded the application of functional DRC assays for personalized disease prevention and treatment. However a recent burst of technical advances, including the highly automated comet chip (104), a proof of concept for integrating DRC in multiple pathways to calculate disease risk (143), and highly multiplexed HCR assays (132), support the notion that measuring DRC could become common clinical practice. To promote this transition, these emerging technologies should be further developed, standardized and validated across multiple laboratories in large (ideally prospective) epidemiological studies employing measurements of multiple DNA repair pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far a lack of standardization and clinical validation, together with the relatively low throughput and labor-intensive nature of most methods of measuring DRC have precluded the application of functional DRC assays for personalized disease prevention and treatment. However a recent burst of technical advances, including the highly automated comet chip (104), a proof of concept for integrating DRC in multiple pathways to calculate disease risk (143), and highly multiplexed HCR assays (132), support the notion that measuring DRC could become common clinical practice. To promote this transition, these emerging technologies should be further developed, standardized and validated across multiple laboratories in large (ideally prospective) epidemiological studies employing measurements of multiple DNA repair pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A second case control study of both OGG1 and AAG activities showed that reduced OGG1 activity and elevated AAG activity were associated with a higher risk of lung cancer, and most important, that a combined score for the two enzyme activities was more strongly associated with cancer risk than either OGG1 or AAG activity alone (142). Recently, this study has been extended to incorporate APE1 into an integrated DNA repair score, termed “OMA” for OGG1, MPG (a.k.a AAG) and APE1; the OMA score varies over a 20-fold range and associates even more strongly with risk of lung cancer (odds ratio 5.6 comparing individuals with the lowest to highest tertile OMA scores) (143). These results emphasize that measuring repair capacity in more than one pathway has the potential to increase biological insight and reveal stronger correlations between DRC and disease risk.…”
Section: The Need For Assays That Measure Drc In More Than One Patmentioning
confidence: 99%
“…Furthermore, GWA studies do not show strong associations between DNA repair gene variants and lung cancer risk. Therefore, we need, as suggested by Weiss et al (17) “larger, well designed functional and epidemiologic studies…to clarify these relationships.” Clearly, using work similar to that of Sevilya et al (1) in well-designed population-based or cohort studies with functional assays, we may be able to make progress in preventing mortality from lung cancer –certainly more than is currently available. Adding the integrated DNA repair OMA score would clearly improve the ability to predict who might benefit from screening.…”
mentioning
confidence: 94%
“…After a successful public health campaign to prevent and stop smoking, the smoking rate has dropped from 42% of the population in 1965 but seems to sit stubbornly at 18% in the United States. At this point in time, at the 50-year mark for the Surgeon General’s Report that smoking causes lung cancer, it is appropriate that Livneh and his group (1) have further developed a potentially valuable set of functional assays as biomarkers to predict lung cancer much earlier.…”
mentioning
confidence: 99%
“…A number of studies support an important role for the NER pathway in lung cancer development. Cleavage and host cell reactivation assays performed in human blood PBMCs, correlate decreased NER repair with an increased lung cancer risk[49,60,61,[64][65][66][67][68][69].…”
mentioning
confidence: 99%